Spatial distribution of soil organic matter in two fields on tidal flat sediments (Zhejiang Province, China) differing in duration of paddy management - Kölbl, A.; Mueller-Niggemann, C.; Schwark, Lorenz; Cao, Z.; Kögel-Knabner, I. (Wiley - V C H Verlag GmbH & Co. KGaA, 2015)
Despite of its ecological and economic importance, only limited information is available on spatial variability of soil organic C (OC) in paddy fields during soil development. To obtain deeper insights into the accumulation and spatial distribution of OC with ongoing paddy management, the present study investigates spatial heterogeneities in puddled topsoil layers, in the plough pan, as well as in the underlying subsoil of a 50- and 300-y old paddy site at the area of Cixi (Hangzhou Bay, E China). Sampling of the plots was done on the basis of a regular, orthogonal grid. The grid combined a large-scale design with distances of 5 m with a small-scale nested sampling ranging within 0.5 to 1 m. Samples have been taken with an auger in three sampling depths: (1) puddled topsoil layer, (2) dense plough layer, (3) mixed subsoil horizon. All samples were analyzed for their OC and total N concentrations as well as for their soil color (lightness value) to assess relationships between soil lightness and OC amount and distribution. The spatial behavior of all analyzed parameters in the different soil layers was investigated by calculating variograms; the degree of spatial dependence was determined by nugget-to-sill ratios. The results show that for each analyzed soil layer, OC and N concentrations were significantly higher in the field with 300 y of paddy management than in the field with 50 y of paddy management. Topsoil OC concentrations changed from 13.8 to 23.6 mg g−1, OC in the plough layer changed from 3.3 to 9.6 mg g−1, and also the subsoil showed a slight increase from 2.9 to 3.3 mg g−1.Although only two points in time were compared, we assume that paddy soil formation is the most likely reason for differences in the spatial distribution of OC between the two sites. Comparing the spatial depth distribution of the 50- and 300-y old paddy sites suggests that the development of a spatial pattern of OC proceeded with time from topsoil to the underlying soil horizons. Measuring soil lightness was insufficient to predict amount and distribution of soil OC in paddy soils, especially in soils with interfering dark-colored burnt straw residues. The degree of spatial homogeneity was equal in the two sites, suggesting that cultivation practices (puddling, levelling, burning and incorporation of straw residues) most likely maintained a rather high random spatial variability of approx. 45%. The spatial pattern of OC in the topsoil was dissimilar to the plough layer, revealing that transport of OC in the plough pan occurred mainly in preferential flow paths along localized cracks and biopores.